Studies on birds of Biratnagar Sub-Metropolis, Nepal - Jha, Kanchan; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2013)
Biratnagar sub-metropolis is a good habitat for several bird species but in the past three decades drastic changes have taken place in the environment of this place because of anthropogenic activities. Several commonly visible birds’ species do not turn out at present. Habitats of birds have shrunk here in such a way that very limited species of birds have become successful to show representatives in this situation. Considering gradual loss of habitats and their inhabitants, an attempt was made to study the present bird status. In the observation of seven months, seventy two species of birds belonging to thirty two families were recorded. The birds recorded, were residents (72.17%), winter visitors (23.59%) and summer visitors (4.16%). DOI: http://dx.doi.org/10.3126/njbs.v1i0.7468 Nepalese Journal of Biosciences 1: 37-40 (2011)